-19 x [4 + (-2)] = - 19 x 4 + (-19) x X
Find X in the following with step if your answer is right I will definitely make you brainliest.
Answers
Answer:
((0-(19•(x4)))+-2)-((0-19x4)+-19x2) = 0
STEP
2
:
Equation at the end of step
2
:
((0 - 19x4) + -2) - (-19x4 - 19x2) = 0
STEP
3
:
Trying to factor as a Difference of Squares
3.1 Factoring: 19x2-2
Theory : A difference of two perfect squares, A2 - B2 can be factored into (A+B) • (A-B)
Proof : (A+B) • (A-B) =
A2 - AB + BA - B2 =
A2 - AB + AB - B2 =
A2 - B2
Note : AB = BA is the commutative property of multiplication.
Note : - AB + AB equals zero and is therefore eliminated from the expression.
Check : 19 is not a square !!
Ruling : Binomial can not be factored as the
difference of two perfect squares
Equation at the end of step
3
:
19x2 - 2 = 0
STEP
4
:
Solving a Single Variable Equation
4.1 Solve : 19x2-2 = 0
Add 2 to both sides of the equation :
19x2 = 2
Divide both sides of the equation by 19:
x2 = 2/19 = 0.105
When two things are equal, their square roots are equal. Taking the square root of the two sides of the equation we get:
x = ± √ 2/19
The equation has two real solutions
These solutions are x = ±√ 0.105 = ± 0.32444
Two solutions were found :
x = ±√ 0.105 = ± 0.32444
Step-by-step explanation: